TANTANGAN DAN STRATEGI PENEGAKAN HUKUM PAJAK DIGITAL DI INDONESIA: STUDI LITERATUR - Loso Judijanto (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The enforcement of digital taxation in Indonesia faces increasingly complex challenges in line with the rapid growth of the digital economy and changes in global business models. This literature study aims to analyse various key obstacles, such as regulatory gaps, low taxpayer compliance, limited surveillance technology, and the complexity of cross-border transactions. This study also identifies strategies that can be implemented, including modernising tax administration through digitalisation, utilising big data and artificial intelligence, strengthening regulations and sanctions, tax education, and international collaboration. The findings indicate that an adaptive and collaborative multidimensional approach is essential to create a fair, effective, and sustainable digital tax system in Indonesia.